La conducta agresiva y su influencia en las relaciones interpersonales de un adolescente - Gómez Campuzano, Celeste Guisela (2020)
The great changes that have been observed as time goes by, in different contexts, and the current demands that behavior represents, do not exceed the current expectations of adolescents in educational centers, the idea of studying through a qualitative approach emerged , aggressive behavior with its main characteristics, with the purpose of establishing, what kind of impact it generates and determining the relationship and level of influence it has in interpersonal relationships, to propose solutions to the problem itself, the study population was an adolescent of an educational center, to which a psychological and psychotherapeutic approach was made through the application of different psychological techniques and tests for the respective diagnosis and treatment.